Fast plastic scintillator with the high light yield - Zhmurin, P.N.; Eliseev, D.A.; Lebedev, V.N.; Pereymak, V.N.; Svidlo, O.V.; Velmozhnaya, E.S. (Functional Materials, 2016)
A fast plastic scintillator (PS) on combined base, consisting of 60 wt.% polystyrene and 40 wt.% N-tolylcarbazole, is presented. Relatively to known fast PS, in which luminescence quenching method is used to reduce the rise time, the new PS has both as the short scintillation flash rise time (σ = 167 ps), as the high light yield 11040 photon/MeV (79 % relatively to anthracene). Such unique combination of the parameters is reached by introduction, into the PS composition, N-tolylcarbazole - a dopant with the strong electron-donating properties and the low ionization potential.